Statins for primary prevention among elderly men and women. (14th October 2021) - Bergami, M; Cenko, E; Yoon, J; Mendieta, G; Kedev, S; Zdravkovic, M; Vasiljevic, Z; Milicic, D; Manfrini, O; Van Der Schaar, M; Gale, C P; Badimon, L; et al.
Abstract: Background: The debate about statins in primary prevention of cardiovascular (CV) disease is still alive, especially in old and very old adults. Purpose: We undertook a propensity match-weighted cohort study to investigate whether statin treatment recommendations translate into improved cardiovascular (CV) outcomes in the current routine clinical care of the elderly. Methods: We included in our analysis 5, 619 people aged 65 years or older from the ISACS (International Survey of Acute Coronary Syndrome) Archives (NCT04008173) who presented to hospital with a first manifestation of CV disease. Participants were stratified as statin users versus nonusers and as old (65 to 75 years) versus very old (76 years or over) adults. We estimated the effects of statins on the most severe clinical manifestation of CV disease, namely ST segment elevation myocardial infarction (STEMI), using inverse probability of treatment weighting models. Estimates were compared by test of interaction on the log scale. Results: The risk of STEMI was much lower in statin users than in nonusers in both patients aged 65 to 75 years (14.7% absolute risk reduction; relative risk [RR] ratio: 0.55, 95% CI 0.45 to 0.66) and those aged 76 years and older (13.3% absolute risk reduction; RR ratio: 0.58, 95% CI 0.46 to 0.72). Estimates were similar in patients with and without history of hypercholesterolemia (interaction test; p value= 0.2408). Proportional reductions in STEMI diminished with female sex in the old (p for interaction=0.002), but not in the very old age (p for interaction=0.26). We also observed a remarkable reduction in the risk of 30- day mortality from STEMI with statin therapy in both age groups (10.2% absolute risk reduction; RR ratio: 0.39; 95% CI 0.23 – 0.68 for patients aged 76 or over and 3.8% absolute risk reduction; RR ratio 0.37; 95% CI 0.17 – 0.82 for patients aged 65 to 75 years old; interaction test, p value=0.4570). Conclusion: Preventive statin therapy in the elderly reduces the risk of STEMI with benefits in mortality from STEMI, irrespective of the presence of a history of hypercholesterolemia. This effect persists after the age of 76 years. Benefits are less pronounced in women. Funding Acknowledgement: Type of funding sources: None.